2010
DOI: 10.1073/pnas.0912765107
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy contributes to the maintenance of microbial diversity

Abstract: Dormancy is a bet-hedging strategy used by a variety of organisms to overcome unfavorable environmental conditions. By entering a reversible state of low metabolic activity, dormant individuals become members of a seed bank, which can determine community dynamics in future generations. Although microbiologists have documented dormancy in both clinical and natural settings, the importance of seed banks for the diversity and functioning of microbial communities remains untested. Here, we develop a theoretical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
673
6
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 766 publications
(723 citation statements)
references
References 52 publications
40
673
6
4
Order By: Relevance
“…In contrast, rare OTUs were detected in a high proportion exclusively in either bulk or potentially active bacterial communities. As suggested for estuarine and coastal ocean waters, the metabolically active rare biosphere of Lake Kivu might be potentially important for the functioning and the temporal dynamics of microbial communities as they shift between seasons [13][14][15].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, rare OTUs were detected in a high proportion exclusively in either bulk or potentially active bacterial communities. As suggested for estuarine and coastal ocean waters, the metabolically active rare biosphere of Lake Kivu might be potentially important for the functioning and the temporal dynamics of microbial communities as they shift between seasons [13][14][15].…”
Section: Discussionmentioning
confidence: 94%
“…Even though potential biases can be introduced during DNA and RNA extraction, complementary DNA (cDNA) synthesis, and PCR amplification [12], parallel comparisons of DNA-and RNA-based pyrosequencing approaches can help differentiate whether abundant taxa are active or whether rare but active taxa exist. In addition, stronger evidence on the links between biogeochemical processes and microbial communities might be obtained if active communities are monitored rather than bulk communities [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that the indigenous bacteria are very sensitive to contaminants and respond rapidly to organic pollutants (Tian et al 2008). In short-term pollution-affected soils, bacterial diversity may be maintained through either natural resistance or dormancy (Jones and Lennon 2010). However, long-term chronic exposure to contamination will have deleterious and unrecoverable effects on the structure and function of the community as the dormancy may not be a useful survival option any longer.…”
Section: Introductionmentioning
confidence: 99%
“…Calculated rarefaction curves, as well as diversity indices (data not shown), revealed that our surveying effort discovered the majority of-yet not all-the bacterial species and phyla (480%) at 3% and 20% genetic distance. The active community yielded a higher number of OTUs than the total BC, resulting in a DNA/RNA ratio of OTU richness ranging from 0.76 to 0.88 and denoting that a significant portion of the rare taxa may be proportionally more active (Jones and Lennon, 2010;Campbell et al, 2011;Wilhelm et al, 2014). The percentage of OTUs that appeared in both, the RNA …”
Section: Bc Compositionmentioning
confidence: 99%